Developing interactive printing techniques using ghostly printing - Maryam Mohammed Mutib Alamari; Razan Mohammed Al-Subaie (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
This study aims to develop interactive printing techniques by employing the concept of "ghostly printing," where the viewer’s shadow becomes part of the artwork. The objective is to explore how shadow-based interaction can enhance the communicative function of art through physical and emotional engagement between the artwork and the audience. The methodology combines theoretical and experimental approaches. The theoretical axis reviews concepts from interactive and conceptual art, while the practical axis involves laboratory-based experimentation using phosphorescent materials and controlled lighting environments. The researcher prepared the exhibition space with light-absorbing surfaces coated in phosphoric acrylic paint. When exposed to white fluorescent light and later to blue tungsten light, these surfaces retained the viewer’s shadow for a limited time, producing an ephemeral visual imprint. Various exposure durations were tested to determine the relationship between light duration and the persistence of the ghostly print. The study concluded that ghostly printing offers a safe and environmentally friendly method to engage audiences in the creative process using accessible materials. A direct correlation was found between the exposure time to blue light and the duration of the resulting print. This interactive method reflects the temporality of human presence and introduces a modern, participatory form of printmaking that aligns with contemporary cultural practices.